ANTIBACTERIAL ACTIVITY OF BIDARA LEAVES (Ziziphus mauritiana L.) ETHANOL EXTRACT AGAINST SOME TEST BACTERIA - Nurrahma, Esti Ayu (Journal Microbiology Science, 2022)
ABSTRACTBidara leaves (Ziziphus mauritiana L.) are one of the traditional plants that contain antibacterial compounds such as alkaloids, flavonoids, saponins, tannins and phenols. This study aimed to determine the antibacterial activity of the ethanol extract of bidara leaves (Ziziphus mauritiana L.) against several test bacteria using the agar diffusion method. This test begins with a screening test using 10 test bacteria and the result is inhibiting the growth of bacteria at a concentration of 0.1%. Then the MIC test was carried out and the result was that a concentration of 0.1% could inhibit and kill the growth of the test bacteria. Then the KBM test was carried out and the results obtained at a concentration of 12.8% could inhibit and kill Eschercia coli and Pseudomonas aeruginosa bacteria, a concentration of 6.4% could inhibit and kill Staphylococcus epidermidis and Vibrio cholerae bacteria, a concentration of 3.2% could inhibit and kill bacteria Staphylococcus aureus, Bacillus sublitis and Streptococcus mutans, a concentration of 1.6% can inhibit and kill Salmonella typhi and Propionibacterium acnes bacteria, and a concentration of 0.8% can inhibit and kill Shigella dysenteriae bacteria. Then, the antibacterial activity of the ethanol extract of bidara leaves (Ziziphus mauritiana L.) was tested using the agar diffusion method and the results showed that the ethanolic extract of bidara leaves (Ziziphus mauritiana L.) had strong potential as an antibacterial against test bacteria with the largest diameter of the inhibition zone at a concentration of 12 ,8% by 15.64 mm.Key Words: Antibacterial, Bidara Leaf (Ziziphus mauritiana L.), Agar diffusion